Cautelar fiscal e combate à sonegação fiscal - Leinz, Vivian (2020)
The conservancy measures were introduced in the Brazilian legal system as a tool to combat tax evasion and as a mechanism made available to the Public Treasury for the safeguarding of its rights during the collection period, thereby preventing the debtor from disposing of his/her assets to the detriment of the creditor. Hence, what happens in practice with these measures? The purpose of this thesis is to answer this inquiry, after observing the efficiency of the precautionary measures in the forensic practice in protecting the Public Treasury´s rights against acts of concealment of assets, confusion of goods, fraudulent conveyance and illegal asset protection and, consequently, in fighting tax evasion. First of all, the importance of tax collection has been highlighted. Thereafter, a panorama of tax evasion was drawn up; included in this topic is the sanction provided by the legal system to the offender of this crime and the causes that contribute to its practice, such as amongst others the protracted collection period. Subsequently the procedure of the conservancy measures was discussed, and some observations about their relevant aspects were made, to arrive at the crux of the thesis: theory applied to practice. Using the case study methodology, eight conservancy measures proposed by the National Treasury in São Paulo between 2018 and 2019 were analyzed. Initially, the studied cases were individually described so as to allow for their continuous comparison, the study of the grounds and requests of the National Treasury, the preliminary ruling and its consequences, the frozen assets, procedural difficulties, judgments and appeals, allowing for an exploration of different variables in order to verify whether the conservancy measures fullfill, in practice, the objectives that fostered their conception. The conclusion is that the conservancy measures, in the way they are used, do not attain the goals they were designed for. Therefore, legislative changes were recommended in order to improve these measures.